Kelimpahan Gastropoda pada Sungai Mengaji di Kabupaten Banyumas - Arumdini, Gustia; Pulungsari, Anastasia Endang; Sastranegara, Moh. Husein (Fakultas Biologi Universitas Jenderal Soedirman, 2024)
River Mengaji originates from a water source on the southern forest slopes of Mount Slamet. Gastropods are important biotic components in river ecosystems and can be used as bioindicators due to their sensitivity to water quality changes. Gastropod abundance is closely related to the physical and chemical parameters of water quality. This study aimed to determine the abundance of gastropods, water quality, and the relationship between gastropod abundance and water quality in River Mengaji, Banyumas Regency. Species gastropod identified samples collected. The relationship between gastropod abundance and water quality was analyzed using Spearman's Rank Correlation. The result showed that the gastropods found in Sungai Mengaji consist of five species, namely Melanoides tuberculata, Sulcosprira testudinaria, Radix rubiginosa, Tarebia granifera, and Filopaludina javanica. The highest abundance of gastropods was observed at Station IV, followed by Stations II, III, and I. Water quality conditions were generally good enough, except for temperature and BOD at Station IV. The high abundance of F. javanica at Station IV is related to the high temperature and BOD conditions in Sungai Mengaji, Banyumas Regency.